The Health Consequences of the Diversion of Resources to War and Preparation for War - Victor W. Sidel; Barry S. Levy (Social Medicine Publication Group, 2024)
Armed conflict damages health in many ways. These include death and disability directly caused by war, destruction of the societal infrastructure that supports health and safety, forced migration of people both within their own country and as refugees to other countries, promotion of violence as a method to settle conflicts and disputes, and the long-term adverse effects on social relationships. This special issue of Social Medicine examines the impact of war on human health from a geographically diverse set of countries and from diverse perspectives. Dr. Andrea Angulo Menasse, a researcher from Mexico City's Autonomous University, documents the very personal story of how the violence of the Spanish Civil War affected one family. In her case study the trauma suffered by Spanish Republicans is traced through three generations and crosses the Atlantic Ocean as the family moves is exiled in Mexico. Dr. Sachin Ghimire from the Centre of Social Medicine and Community Health of the Jawaharlal Nehru University reports on his fieldwork in Rolpa, Nepal, the district from which the Nepal Civil War (also called the People's War) originated in 1996. Based on 80 interviews, he documents the difficulties faced by health care workers as they negotiated the sometimes deadly task of remaining in communities where control alternated between Nepalese Special Forces and the Maoist rebels. Finally, Colombian researcher, Carlos Iván Pacheco Sánchez, from the University of Rosario in Bogota, brings an epidemiologist's tools to examine the impact of the ongoing armed conflict in the border Department of Nariño. His discussion is informed by the current debate over health care in Colombia where a recent Constitutional Court decision has found that the current health care system violates the right to health. These three papers amply demonstrate the depth, breadth and relevance of contemporary social medicine.